Research on an Adaptive Motion Planning Method for Multi-joint Hyper-redundant Robots - Luo Shuangbao; Zeng Fengfei; Zeng Xiaoshan; Qiang Hua; Wang Xiaoyang (Jixie chuandong)
An adaptive motion planning method is proposed for the problems of complex kinematic solution, large configuration deviation of traditional multi-joint hyper-redundant robots. Firstly, an improved trajectory tracking algorithm is proposed for the task requirement of entering and leaving a narrow working space. By discrete target trajectory and segment fitting, the computational effort can be reduced, and the adaptive trajectory tracking control can be achieved. Then a bidirectional iterative tractor trajectory planning algorithm is proposed for the robot base fixed working condition. The target trajectory is obtained based on the end-traction method. By using the geometric property of the tractrix progressive convergence, the motion range of joints near the base is gradually reduced, the stability is improved, and the energy consumption is reduced. The adaptive trajectory control in the base fixed state is achieved through bi-directional iterative tractrix accelerated convergence. Finally, a simulation model containing 12 joints and (24+1） degrees of freedom is constructed， and the effectiveness of the adaptive motion planning method for the entire process of robot operation is verified.